Global players and the Indian car industry trade, technology and structural change - Singh, Jatinder (Critical political economy of South Asia, 2018)
This book is one of the first critical analyses of the automobile industry in India. It studies the sector in general and the passenger car industry in particular, and provides valuable insights into the operation of Foreign Direct Investment (FDI) companies in a technology-intensive industry under changing economic regimes. The volume underlines the influence of the changing nature of foreign investment, the impact of economic reforms, technology regimes and industrial policy on growth, structural changes and development. It offers a detailed account of the trade performance of manufacturers in India's passenger car industry. It also looks at successful cases to draw policy lessons towards encouraging quality FDI and developing India as a base for world production. A useful addition to industry studies in India, this book with its wide coverage and contemporary analyses will interest scholars and researchers of economics, Indian economy and industrial policy, industrial economics, automobile industry and manufacturing sector, development economics and international economics. It will also appeal to policymakers, practitioners and industrial associations